Optical deposition of carbon nano-particles for functional photonics devices - Tan, Wai Kiat. (2013)
Fibre laser that generates ultra-short pulse at high repetition rate has many uses in various applications. To generate such pulses, mode-locking is employed, which is a technique that allows the generation of ultra-short pulses usually in the order of picoseconds or femtoseconds and at a repetition rate higher than or equal to megahertz range.